2018
DOI: 10.1007/s00106-018-0522-5
|View full text |Cite
|
Sign up to set email alerts
|

Submuköse Gaumenspalte und kongenital kurzes Velum: Effekte der operativen Intervention

Abstract: Surgical intervention was particularly effective in children younger than 5 years. Syndromic diseases are disproportionately associated with soft palate defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…The present study showed that children with a submucous cleft routinely present late (44.0 months, range 0-150, SD = 37.0). This is just a bit earlier than in the study of Reiter et al who found a mean age of diagnosis at 4.9 years and comparable with Brosch et al who found a mean age at 4.2 years [24,25]. In the present study and Reiter's study, there is a very wide range, meaning that SMCP is not always noted early in life.…”
Section: Discussionsupporting
confidence: 72%
“…The present study showed that children with a submucous cleft routinely present late (44.0 months, range 0-150, SD = 37.0). This is just a bit earlier than in the study of Reiter et al who found a mean age of diagnosis at 4.9 years and comparable with Brosch et al who found a mean age at 4.2 years [24,25]. In the present study and Reiter's study, there is a very wide range, meaning that SMCP is not always noted early in life.…”
Section: Discussionsupporting
confidence: 72%